2018
DOI: 10.1002/eco.2023
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the water repellency and storage of different species of deadwood based on decomposition rate in a temperate climate

Abstract: The aim of this study is to demonstrate the changes to the physical properties and water repellency (WR) of deadwood depending on the species and rate of decomposition. An innovative element of this study is the measurement of droplets' contact angle to the surface of the wood. Five species of trees at three different stages of decomposition were selected for the present study. The deadwood Silver Fir (Abies alba), Common Hornbeam (Carpinus betulus), Common Ash (Fraxinus excelsior), Common Alder (Alnus glutino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The release of carbon from decomposing wood in successive stages of decay subsequently increases soil water content, porosity, and soil aggregation. A previous study confirmed the intensification of dissolved organic carbon release in the subsequent stages of wood decomposition [5] and an increase in the concentration of cations with the advancement of the deadwood decay class [9]. The cations released from deadwood also affect the physical properties of the soil by shaping the structure.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The release of carbon from decomposing wood in successive stages of decay subsequently increases soil water content, porosity, and soil aggregation. A previous study confirmed the intensification of dissolved organic carbon release in the subsequent stages of wood decomposition [5] and an increase in the concentration of cations with the advancement of the deadwood decay class [9]. The cations released from deadwood also affect the physical properties of the soil by shaping the structure.…”
Section: Discussionsupporting
confidence: 54%
“…The present study also showed significantly higher carbon content in soil under the influence of strongly decomposed wood (fourth and fifth DC) regardless of the species. Deadwood influences soil properties through its fragmentation and dissolved organic carbon leaching [5,30]. The release of carbon from decomposing wood in successive stages of decay subsequently increases soil water content, porosity, and soil aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the high concentration of DOC in leachates from deadwood in V decay class can be explained by its texture and fragmentation. The wood in V decay class is characterized by soft and loose texture which results in greater water capacity and hydrophilicity (Błońska et al 2018). The high DOC and TN concentration can be also associated with the term of the experiment which including snow melt period.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of obtained leachates is associated with the physical characteristics of wood, especially density, and porosity. As the degree of decomposition increases, wood absorbs water more quickly (Błońska et al 2018).…”
Section: Discussionmentioning
confidence: 99%